Discovery of Optimal Interplay between Grafting Ratio and Side-Chain Interval in Adhesive Polymer Binders for Lithium-Ion Batteries - Won, Gwangbin; Jo, Min Seo; Jeong, Yeong Hun; Seo, Sinyoung; Kim, Seunghyeon; Kwon, Da-Sol; Jeong, Daun; Shim, Jimin (AMER CHEMICAL SOC, 2025)
Polymer binders play a critical role in ensuring adhesion and mechanical stability in lithium-ion battery electrodes. Here, we systematically explore the architectural influence of poly(vinylidene fluoride)-graft-poly(acrylic acid) (PVDFA) binders synthesized via atom transfer radical polymerization. By tuning the grafting ratio and side-chain interval, we identify an optimal structure that maximizes adhesion and cycling stability. The optimized binder (22 mol % grafting, similar to 300 interval) outperforms conventional PVDF in electrochemical performance. This study highlights the important role of fine-tuning polymer architecture in governing interfacial and mechanical properties and provides fundamental insights for the rational design of advanced adhesive binders for high-performance lithium-ion batteries.